Rough fuzzy image analysis : foundations and methodologies - Pal, Sankar K.; Peters, James F. (Boca Raton, Florida : CRC Press/Taylor & Francis, 2010)
Fuzzy sets, near sets, and rough sets are useful and important stepping stones in a variety of approaches to image analysis. Emphasizing the utility of fuzzy, near, and rough sets in image analysis, this title introduces the fundamentals and applications in rough fuzzy image analysis
1. Cantor, fuzzy, near, and rough sets in image analysis -- 2. Rough-fuzzy clustering algorithm for segmentation for brain MR images -- 3. Image thresholding using generalized rough sets -- 4. Mathematical morphology and rough sets -- 5. Rough hybrid scheme: an application of breast cancer imaging -- 6. Applications of fuzzy rule-based systems in medical image understanding -- 7. Near set evaluation and recognition (NEAR) system -- 8. Perceptual systems approach to measuring image resemblance -- 9. From tolerance near sets to perceptual image analysis -- 10. Image segmentation: a rough-set theoretic approach -- 11. Rough fuzzy measures in image segmentation and analysis -- 12. Discovering image similarities. tolerance near set approach
Includes bibliographical references and index
Keywords: Fuzzy sets; Image analysis